Analysis of Factors Influencing Regional Financial Independence in Regencies/Cities in Yogyakarta - Indriati, Faustina Raissa; Nihayah, Annis Nurfitriana (Efficient: Indonesian Journal of Development Economics, 2026)
This study aims to determine the factors influencing regional financial independence in regencies/cities in the Special Region of Yogyakarta Province. This study uses panel data regression analysis which is a combination of cross-sectoral data from 5 regencies/cities in the Special Region of Yogyakarta Province and time series data from 2014-2024. The results of this study indicate that special funds, regional revenues, and special allocation funds have a significant positive influence on regional financial independence. Meanwhile, general allocation funds have a negative but insignificant influence on regional financial independence in regencies/cities in the Special Region of Yogyakarta Province. Regional financial independence can be improved by optimizing regional revenues and utilizing specific and asymmetric fiscal transfers so as not to rely on transfer funds that tend not to encourage regional financial independence.